Folkloristic elements in the poetry of K. Donelaitis - Radzevičius, Algimantas (Respectus Philologicus, 1999)
The work by the first “classic” in Lithuanian literature is at present generally related to its roots in ethnic folklore in a narrow and negative way. In this article we express the turn-traditional opinion that a study of Donelaitis’ relation of folklore reveals rich resources employed by the father of Lithuanian poetry and shows how folklore helped shape his artistic and literary portrayals, his expression of human dealings in terms of the non-human world of nature, his personification of natural processes, and his use of hyperbole to describe human behaviour. The close ties between belles-lettres and folklore is here understood as characteristic of Renaissance developments in the sixteenth century. This development, which ran counter to neoclassical scorn of folklore, reached its culmination in the Lithuanian-German culture and literature of Donelaitis’ homeland, Greater Lithuania, in the eighteenth century.